Perbandingan Efektivitas Pendidikan Kesehatan Gigi dan Mulut Melalui Media Aplikasi Whatsapp dengan Media Alat Peraga terhadap Perubahan Perilaku Siswa SMAN 3 Padang - Nadhim Sechillia Arman; Lendrawati Lendrawati; Surma Adnan (Faculty of Dentistry Universitas Andalas, 2021)
Dental health education can be applied by the Whatsapp Messenger and learning tools. Whatsapp is a free messenger application that is widely used by internet users including teenagers in sending multimedia with simple text messages. Learning tools are one of the learning media commonly used in dental health education activities. Objective: To find out the comparison of dental health education through the Whatsapp Messenger with learning tools on behavioral changes of students at SMAN 3 Padang. Research method: This study used a quasy experimental with pret and post-test design. The research sample was divided into groups containing through the media the Whatsapp Messenger and groups with learning tools. The Wilcoxon trial to compare the pretest and posttest of each group and the Mann Whitney test to compare effectiveness in the Whatsapp group and learning tools group. Results: There was a significant change in increasing knowledge, attitudes, actions and behaviors in Whatsapp Group a learning tools group after getting trials (p<0.05). There is a difference in effectiveness between Whatsapp Media and learning tools media in increasing changes in knowledge, actions and behavior (p<0.05), but there is no difference in effectiveness between Whatsapp media and learning tools media in increasing attitude changes (p>0.05). Conclusion: There is a difference in dental health education through the application of Whatsapp media with teaching aids media to the changing functions of students of SMAN 3 Padang